Preface - Editorial Team, EICCS (Evolution of Information, Communication and Computing System, 2022)
This book chapter is produced by Internet of Things (IoT) Focus Group, Faculty of Electrical and Electronic Engineering. This book chapter is an introduction to a number of the topics in Internet of Things (IoT), which focusing on the tracking and monitoring systems. All topics described the design and system development related to IoT. The presented topics have been selected to give an idea to engineering students in order to design the IoT systems. This book chapter is generally suitable as complement to integrated design and final year project of engineering students.